2010
DOI: 10.1177/1545968310368963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Task-Oriented Training Content on Skilled Arm-Hand Performance in Stroke: A Systematic Review

Abstract: The task-oriented training was operationalized with 15 components. The number of components used in an intervention aimed at improving arm-hand performance after stroke was not associated with the posttreatment effect size. Certain components, which optimize storage of learned motor performance in the long-term memory, occurred more in studies with larger treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 47 publications
4
108
1
Order By: Relevance
“…3) The fact that the patient's forearm is attached to the gimbal impedes the open chain action that is characteristic for upper extremity movement. 4) It is known that feedback is an important training characteristic that is [23].…”
Section: Discussionmentioning
confidence: 99%
“…3) The fact that the patient's forearm is attached to the gimbal impedes the open chain action that is characteristic for upper extremity movement. 4) It is known that feedback is an important training characteristic that is [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many previous studies of upper limb training have emphasized that stroke rehabilitation training paradigm is needed to provide more detailed information about the components of movement (Basteris et al 2014;Pollock et al 2014). In particular, it was highlighted that specific and repetitive tasks are most effective in acceleration of neuroplasticity of the brain (Hubbard et al 2009;Timmermans et al 2010). Liao et al (2012) reported that repetitive robot-assisted upper limb rehabilitation can After 4 weeks of robot-assisted reach training for 3 directions, significant improvement on upper extremity kinematic performance (movement velocity) was observed in individuals with chronic stroke (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Feedback is also associated with high training effects [28]. Next to supporting motor learning, feedback can positively influence motivation, self-efficacy, and compliance [29,30].…”
Section: Us"em: Concept Overviewmentioning
confidence: 97%